2014
DOI: 10.1158/1535-7163.mct-14-0243
|View full text |Cite
|
Sign up to set email alerts
|

miR-185 Suppresses Tumor Proliferation by Directly Targeting E2F6 and DNMT1 and Indirectly Upregulating BRCA1 in Triple-Negative Breast Cancer

Abstract: Breast cancer is a major public health problem all over the world, and the current treatment strategies are not potent enough for some patients, especially those with triple-negative breast cancer (TNBC). Recent studies have demonstrated that microRNAs (miRNA) play vital roles in the development of TNBC. In this study, we found that miR-185 was strongly downregulated in TNBC tissues and cell lines and that its expression levels were associated with lymph node metastasis, clinical stage, overall survival, and r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 54 publications
1
61
2
Order By: Relevance
“…miRNAs play a vital role in many crucial cellular processes, including apoptosis, differentiation, invasion, and proliferation (32)(33)(34). The abnormal expression of miRNA has been reported in many cancers, including breast (35), gastric (36), colorectal (37), and liver cancers (38), as well as leukemia (39) and lymphoma (40). miR-124 has been described as a brain-specific miRNA in mammals, and may play a role in defining and maintaining neuron-specific characteristics (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play a vital role in many crucial cellular processes, including apoptosis, differentiation, invasion, and proliferation (32)(33)(34). The abnormal expression of miRNA has been reported in many cancers, including breast (35), gastric (36), colorectal (37), and liver cancers (38), as well as leukemia (39) and lymphoma (40). miR-124 has been described as a brain-specific miRNA in mammals, and may play a role in defining and maintaining neuron-specific characteristics (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some tumor-suppressor miRNAs inhibit oncogenic transcription factors, including Myc (let-7 b, 7 c and 7 d) [78], B-cell CLL/lymphoma 6 (BCL6, mir-127-3p) [85], v-ets avian erythroblastosis virus E26 oncogene homolog 1 (ETS1, mir-125 a, miR-125 b) [84], v-ets avian erythroblastosis virus E26 oncogene homolog 2 (ETS2, mir-320) [102], SRY box 9, (SOX9, miR-140) [86] and E2F transcription factor 6 (E2F6, miR-185) [95], all of which were found to be downregulated in DCIS (Table 1). During the tumorigenic transformation process, premalignant breast epithelial cells lose cell polarity and gain deregulated proliferation, leading to rapid growth and formation of the tumor mass.…”
Section: Mirnas Downregulated In Dcismentioning
confidence: 99%
“…Some of the miRNAs downregulated in DCIS are implicated in the downregulation of anti-apoptotic factors, including BCL2 (miR-143, miR195) [88,99,123], Survivin (miR-143) [89], Bcl-w (miR-497) [105] and 14-3-3f (miR-451) [103] (Table 1). In addition, these identified tumor-suppressive miRNAs also functionally target other biological processes including cell-cycle progression (Cyclin D1, targeted by miR-143) [89], angiogenesis (vascular endothelial growth factor A [VEGFA], targeted by miR-145 and miR-185) [91,96], epigenetic regulation (TET1-3, targeted by miR-22; DNA (cytosine-5)-methyltransferase 1 [DNMT1], targeted by miR-185) [79,95], Rho-dependent signal transduction (RTKN, targeted by miR-145) [92], invasion (ADP ribosylation factor 6 [ARF6], targeted by miR-145; CD147, targeted by miR-22; Six1, targeted by miR-204; Smad3, targeted by miR-489) [80,93,100,104] and degradation of the extracellular matrix (ECM) (urokinase plasminogen activator, uPA, targeted by miR-193 b) [97] (Table 1).…”
Section: Mirnas Downregulated In Dcismentioning
confidence: 99%
“…Each type of miRNA may modulate the expression of numerous mRNAs simultaneously; therefore, miRNAs serve critical roles in biological functions, including cell proliferation, cell cycle progression, migration, invasion, metastasis, apoptosis, metabolism and the immune response (12)(13)(14)(15)(16)(17)(18). Accumulating studies have indicated that there are associations between miRNA expression and the clinical features of patients with cancer, including tumor size, tumor-node-metastasis (TNM) stage, development, survival time, disease recurrence and metastasis (19)(20)(21)(22). miRNAs have been reported to be frequently dysregulated in various types of human cancer, and may function as tumor suppressors or oncogenes in tumorigenesis and tumor development (23).…”
Section: Introductionmentioning
confidence: 99%